Quality Improvement Arabic Education with Transformation of Arabic Learning Media - Faruq, Umar; Nurcholis, Ahmad; Hamid, Muhammad Abdul; Rudisunhaji, Muhamad Asngad; Marpuah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2022)
Various aspects of the world of education, including learning media have been shifted by Covid-19. This research aims to identify and evaluate the use of Arabic learning media design at the Raden Paku Modern Islamic Boarding School in Trenggalek. Employing a qualitative approach, this study analyzed descriptive data in the form of speech or writing and the observable behavior of the research subjects. Online news articles and student interviews served as the sources for the study's data. Online news mapping was confirmed with student groups as participants in the study, meanwhile, interviews were conducted with 30 students. The results showed that the Raden Paku Modern Islamic Boarding School is an institution that has a good vision and mission in the religious field. Therefore, the process of learning Arabic was greatly aided by the guidance of teachers (ustadzah). In addition, ustadzah actively participated in educational events and chose the top learning materials for the lessons she was teaching. Such as visual media and audio media which aim to increase interest in learning and increase learning stimulation for students. Digital-based Arabic teaching media is more effective in strengthening student competencies so as to encourage student achievement. The transformative teaching media in question has the criteria of being easily accessible, helping students to be more creative, and encouraging students to be more independent.